Importance of polyelectrolyte modification for rectifying the ionic current in conically shaped nanochannels. Issue 7 (3rd February 2017) - Hsu, Jyh-Ping; Wu, Hou-Hsueh; Lin, Chih-Yuan; Tseng, Shiojenn
Abstract : Regulating the ICR behavior of a conical nanochannel can be achieved by modifying its surface appropriately. Abstract : Due to their specific geometry, conical nanochannels/nanopores are capable of exhibiting several interesting electrokinetic phenomena including, for example, ion concentration polarization (ICP) and ion current rectification (ICR). Extending previous analyses, we consider two types of nanochannels: only the inner surface of a nanochannel is functionalized by a polyelectrolyte (PE) layer in a type I nanochannel, and both its outer and inner surfaces are functionalized in a type II nanochannel. The influences of the thickness of a double layer and that of the PE layer on ICR are examined through numerical simulation. We show that the ICP of a type I nanochannel is more significant than that of the corresponding type II nanochannel. The behavior of the rectification factor of the former as the bulk salt concentration varies also differs significantly from that of the latter. In particular, the rectification factor of a type I nanochannel at a low bulk salt concentration shows an inversion.